Efficacy, safety, and risk factors for failure of standalone ab interno gelatin microstent implantation versus standalone trabeculectomy - Schlenker, Matthew; Hengerer, Fritz (Ophthalmology, 2017)
Purpose: To compare the efficacy, safety, and risk factors for failure of standalone ab interno gelatin microstent implantation with mitomycin C (MMC) versus trabeculectomy with MMC. Design: International, multicenter, retrospective interventional cohort study. Participants: Three hundred fifty-four eyes of 293 patients (185 microstent and 169 trabeculectomy) with no prior incisional surgery. Methods: Consecutive eyes with uncontrolled glaucoma underwent microstent or trabeculectomy surgery from January 1, 2011 through July 31, 2015 at 4 academic ophthalmology centers: Toronto, Canada; Frankfurt, Germany; Salzburg, Austria; and Leuven, Belgium. Main Outcome Measures Primary outcome measure was hazard ratio (HR) of failure, with failure defined as 2 consecutive intraocular pressure (IOP) readings of <6 mmHg with vision loss or >17 mmHg without glaucoma medications (complete success) at least 1 month after surgery despite in-clinic interventions (including needling). Secondary outcome measures included IOP thresholds of 6 to 14 mmHg and 6 to 21 mmHg and same thresholds allowing for medications (qualified success), interventions, complications, and reoperations. Results: Baseline characteristics were similar, except more men (56% vs. 43%), younger patients (average, by 3 years), better preoperative visual acuity (22% vs. 32% with 0.4 logarithm of the minimum angle of resolution vision or worse), and more trabeculoplasty (52% vs. 30%) among microstent eyes. The adjusted HR of failure of the microstent relative to trabeculectomy was 1.2 (95% confidence interval [CI], 0.7-2.0) for complete success and 1.3 (95% CI, 0.6-2.8) for qualified success, and similar for other outcomes. Time to 25% failure was 11.2 months (95% CI, 6.9-16.1 months) and 10.6 months (95% CI, 6.8-16.2 months) for complete success and 30.3 months (95% CI, 19.0-∞ months) and 33.3 months (95% CI, 25.7-46.2 months) for qualified success. Overall, white ethnicity was associated with decreased risk of failure (adjusted HR, 0.49; 95% CI, 0.25-0.96), and diabetes was associated with increased risk of failure (adjusted HR, 4.21; 95% CI, 2.10-8.45). There were 117 and 165 distinct interventions: 43% and 31% underwent needling, respectively, and 50% of trabeculectomy eyes underwent laser suture lysis. There were 22 and 30 distinct complications, although most were transient. Ten percent and 5% underwent reoperation (P = 0.11). Conclusions: There was no detectable difference in risk of failure and safety profiles between standalone ab interno microstent with MMC and trabeculectomy with MMC.